PEMAHAMAN CHOUKAI MAHASISWA ANGKATAN 2020 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU PADA PODCAST SAKURA TIPS - Dwisyafirantini Dwisyafirantini; Nana Rahayu; Merri Silvia Basri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to find out how the choukai understanding of the 2020 students of the Japanese Language Education study program at the University of Riau on the sakura tips podcast. This study uses a quantitative descriptive research method. The population is the class of 2020 students, totaling 27 people. The instrument of this research is in the form of a test. The data analysis technique used descriptive statistics. The results showed that the choukai understanding of the class of 2020 students towards the sakura tips podcast obtained an average score of 66% in the good category.Key Words: Understanding, Choukai, Podcast